Leucoanthocyanidin Reductase 3 (PaLAR3) Locus in Norway Spruce (Picea abies) and Its Link to Resistance Against Heterobasidion parviporum - Durodola, Blessing; Hanström, Neea; Blumenstein, Kathrin; Haapanen, Matti; Hantula, Jarkko; Kashif, Muhammad; Piri, Tuula; Terhonen, Eeva (Wiley-Blackwell, 2024)
Heterobasidion parviporum is a fungal pathogen that is drastically damaging Norway spruce (Picea abies) in Europe. The infections will result in root and stem rot, causing significant economic losses for forest owners. Previous studies have shown that the PaLAR3 gene, which encodes the leucoanthocyanidin reductase enzyme, can increase resistance to H. parviporum in Norway spruce. The presence of the B allele at the PaLAR3 locus has been associated with higher (+)-catechin concentrations and increased enzyme production in inoculation experiments, resulting in inhibited pathogen growth. The control of H. parviporum involves a multifaceted approach, including silvicultural and sustainable forestry practices, genetic resistance and chemical/biological control. In this study, we determined the PaLAR3 genotypes in a representative sample of Norway spruce breeding materials from southern Finland and examined their effect on necrosis caused by H. parviporum in spruce stems. The results showed that the homozygous PaLAR3BB genotype was present in only 9% of the trees. However, the necrotic area interacted with homozygous PaLAR3BB under low-water treatment. These findings support the idea that the PaLAR3 locus may be a valuable marker for identifying P. abies resistance to different strains of Heterobasidion parviporum.
Keywords: molecular marker; root rot; tree breeding